New molecular interaction of IIANtr and HPr from Burkholderia pseudomallei identified by X‐ray crystallography and docking studies1. Issue 9 (23rd August 2013) - Kim, Mi‐Sun; Lee, Hasup; Heo, Lim; Lim, Areum; Seok, Chaok; Shin, Dong Hae
<x xml:space="preserve">Abstract</x> The nitrogen‐related phosphoenolpyruvate phosphotransferase system (PTSNtr) is involved in controlling ammonia assimilation and nitrogen fixation. The additional role of PTSNtr as a regulatory link between nitrogen and carbon utilization in Escherichia coli is assumed to be closely related to molecular functions of IIANtr in potassium homeostasis. We have determined the crystal structure of IIANtr from Burkholderia pseudomallei (BpIIANtr), which is a causative agent of melioidosis. The crystal structure of dimeric BpIIANtr determined at 3.0 Å revealed that its active sites are mutually blocked. This dimeric state is stabilized by charge and weak hydrophobic interactions. Overall monomeric structure and the active site residues, Arg51 and His67, of BpIIANtr are well conserved with those of IIANtr enzymes from E. coli and Neisseria meningitides. Interestingly, His113 of BpIIANtr, which corresponds to a key residue in another phosphoryl group relay in the mannitol‐specific enzyme EIIA family (EIIAMtl), is located away from the active site due to the loop connecting β5 and α3. Combined with other differences in molecular surface properties, these structural signatures distinguish the IIANtr family from the EIIAMtl family. Since, there is no gene for NPr in the chromosome of B. pseudomallei, modeling and docking studies of the BpIIANtr–BpHPr complex has been performed to support the proposal on the NPr‐like activity of BpHPr. A potential dual role of BpHPr as a nonspecific phosphocarrier protein interacting with both sugar EIIAs and IIANtr in B. pseudomallei has been discussed. Proteins 2013. © 2013 Wiley Periodicals, Inc.